PROSPEK PENGEMBANGAN INDUSTRI BORDIR/SULAMAN DI KOTA PEKANBARU - Rezzy Andriani; Mardiana '; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine whether the industry Embroidery /embroidery in Pekanbaru has good prospects for development. This research was conducted in the city of Pekanbaru by using primary data and secondary dataobtained from the Department of Industry and Commerce in the city of Pekanbaru and Pekanbaru City Central Statistics Agency (BPS). Data analysis method used is to use the Payback Period (PP), Benefit Cost Ratio (B / C Ratio), Net Present Value (NPV) and Internal Rate Of Return (IRR). From the research that has been done by the author, can be seen the average income of industrialists embroidery / needlework is Rp. 27,247,273 per year. With Payback period is 1 year and 5 months 19 days, Benefit Cost Ratio (B / C Ratio) amounted to 1,101, Net Present Value (NPV) is Rp. 67,833,089, and Internal Rate Of Return (IRR) is approximately 66.2%.Industry so small embroidery / needlework in Pekanbaru City declared eligible to run.Keywords : Prospect, Industrial Development, PP, B/C, NPV, IRR